شرط الواقف وعلاقته بالإدارة الحديثة للمؤسسات الوقفية – دراسة مقارنة: Endower Requirements and Its Relationship to Modern Management at Waqf Institutions - A Comparative Study - Muhammad Bn Al-Sheikh Abdullah , (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
ملخص هناك علاقة وثيقة بين شرط الواقف والإدارة الحديثة سواء كعلاقة تنظيمية أو علاقة إدارية صرفة، وذلك أن شرط الواقف من النظرة الفقهية يعتبر معيار في تحديد ماهية وصلاحيات ناظر الوقف، ومن هنا من الأهمية بمكان معرفة الخلفية الشرعية لشروط الواقف حتى نستطيع أن نتصور علاقتها بالمؤسسات الوقفية الحديثة، تأتي هذه الدراسة للكشف عن هذه الشروط ومعالجة آثارها وبيان خصوصيتها لتقييم ما يجب وما يحرم منها وفق منظور فقهي، وما يتعلق بالإدارة وما يعززها من المنظور الإداري الحديث، استخدم الباحث في هذا البحث المنهج الوصفي التحليلي، وشيء من المنهج المقارن، وذلك بالتحليل العميق للنصوص الفقهية ذات الصلة بموضوع الدراسة. الكلمات المفتاحية: شرط الواقف، الإدارة الحديثة، المؤسسات الوقفية الحديثة Abstract There is a close relationship between the condition of the endower and the modern administration, whether as an organizational relationship or a purely administrative relationship, because the condition of the endower from the jurisprudential view is considered a criterion in determining the nature and powers of the endowment overseer Hence, it is important to know the legal background of the conditions of the endowment, so that we can imagine their relationship to the modern endowment institutions .This study comes to reveal these conditions, treat their effects, and clarify their privacy, to assess what should and what is forbidden according to a jurisprudential perspective, and what is related to management and what enhances it from a modern administrative perspective. In this research, the researcher used the descriptive analytical method, and some of the comparative method, by deeply analyzing the jurisprudential texts related to the subject of the study. Kyewords: condition of the endower, modern administration, modern endowment institutions